Danmu subtitling as a self-regulative practice: a descriptive discourse analysis of Bilibili danmu subtitles from ethical perspectives - Zeng, Duo (Frontiers in Psychology, 2025)
Translation ethics is an important aspect of Translation Studies that has gained increasing attention in recent years. From an ethical perspective, this study investigates the onscreen commenting system: danmu subtitling, an emergent non-professional and collaborative translation practice popular in Asian communities. Adopting, modifying and expanding Andrew Chesterman’s models of translation ethics, i.e., representation ethics, service ethics, communication ethics, norm-based ethics and ethics of professional commitment and proposing an ethics of digital technology, this study delves into how ethical principles explain the user-generated danmu subtitles. Descriptive discourse analysis is performed in this study observing an episode of Tamara’s World (uploaded with no subtitles or translations), an English variety show, examining 296 translation-related instances among 1,490 danmu comments. Findings indicate that multiple ethical models elucidate danmu subtitling practices, which encounter distinct ethical conflicts. Consequently, adaptive regulation is proposed to resolve these conflicts.